Effect of Hyperthermic Intraperitoneal Perfusion Chemotherapy Combined with Radical Surgery and Capecitabine on Stage III Gallbladder Cancer - Sulai Liu; Zhendong Zhong; Weimin Yi; Zhangtao Yu; Zhihua Zhang; Guoyi Xia; Bo Jiang; Yinghui Song; Chuang Peng (Canadian Journal of Gastroenterology and Hepatology)
Purpose. The aim of the study was to investigate the effect of hyperthermic intraperitoneal perfusion chemotherapy (HIPEC) combined with radical surgery and capecitabine on stage III gallbladder cancer. Method. Seventy-eight patients with stage III gallbladder cancer treated in our hospital between December 2015 and April 2019 were retrospectively enrolled. Depending on the treatment approach, the patients were divided into the control group (radical surgery and capecitabine) and the HIPEC group (hyperthermic intraperitoneal perfusion chemotherapy combined with radical surgery and capecitabine). The patients were followed up by outpatient or through telephone until April 1, 2020. SPSS 19.0 software was applied for data analysis. Survival analysis was performed using the Kaplan–Meier method and parallel log-rank test. Results. There were 43 cases in the control group and 35 cases in the HIPEC group. There were no significant differences in operation time, lymph node metastasis, microvascular infiltration, and nerve invasion; there was no significant difference in postoperative complications between the two groups (P>0.05). The average hospitalization time of the HIPEC group was 23.0 ± 6.9 days, which was longer than the 20.0 ± 5.8 days of the control group (P<0.05). The body temperatures of HIPEC group patients at 0 h and 6 h after operation were higher than those of patients in the control group (P<0.05); however, the body temperature of the two groups gradually became the same at 12–24 h after operation. There was no liver and kidney damage in the two groups after surgery. The platelets in the HIPEC group were less than those in the control group (P<0.05). The median survival time of HIPEC was 19.2 months, which was longer than 15.3 months in the control group. The 1-year survival rates of the two groups were 91.43% vs. 76.71%, and the 2-year survival rates were 26.29% vs. 17.53%, respectively (P<0.05). Conclusion. HIPEC combined with radical surgery and capecitabine for stage III gallbladder cancer can effectively prolong survival time without increasing surgery-related complications.